Cover Picture: Engineering inorganic lead halide perovskite deposition toward solar cells with efficiency approaching 20%. Issue 1 (12th March 2021) - Qiu, Fa‐Zheng; Li, Ming‐Hua; Qi, Jun‐Jie; Jiang, Yan; Hu, Jin‐Song
Abstract : Inorganic perovskite materials have gained tremendous attention owing to their superior chemical and thermal stability. In article number 2021, 2, 66–83, Jin‐Song Hu and co‐workers report a clear roadmap to fabricate high‐quality inorganic perovskite films by tunning the precursor crystallization kinetics, performing post‐deposition treatments, and passivating surface/interface defects, which is beneficial to accelerate the development of inorganic perovskite solar cells towards an efficiency beyond 20%. (DOI: 10.1002/agt2.19 )